EFFECTIVENESS OF ACCELERATING STUNTING REDUCTION THROUGH CONVERGENCE ACTIONS IN THE NORTH JAKARTA ADMINISTRATIVE CITY - Citrawati, Citrawati; Kridawati, Atik; Sunita, Anna (Indonesia Epidemiological Journal, 2024)
Background: Stunting is a significant health problem in Indonesia, including in urban areas such as North Jakarta, which requires integrated interventions to reduce the incidence. Objectives: This study aims to evaluate the effectiveness of the accelerated stunting reduction program through convergence action and analyze the driving and inhibiting factors, including innovations in the North Jakarta Administrative City. Methods: This study used descriptive analysis with a combined quantitative and qualitative approach, collecting primary data through questionnaires and interviews, as well as secondary data from the convergence action implementation report. Program effectiveness was measured through source, process, and target approaches. Results: The study shows that the accelerated stunting reduction program is quite effective, although its implementation is not yet optimal. Driving factors include budget support, regulations, human resources, as well as cross-sector collaboration and innovation from the private sector. Barriers include poverty, lack of healthy living behaviors, limited community knowledge, and the unavailability of an integrated data management system. Conclusion: Accelerating stunting reduction through convergence actions is considered quite effective, although there are still some challenges that need to be overcome, such as poverty and low community knowledge.